Wage Bargaining and Labor Market Policy with Biased Expectations - Almut Balleer; Georg Duernecker; Susanne Forstner; Johannes Goensch (Center for Economic Studies and ifo Institute (CESifo), 2023)
Recent research documents mounting evidence for sizable and persistent biases in individual labor market expectations. This paper incorporates subjective expectations into a general equilibrium labor market model and studies the implications of biased expectations for wage bargaining, vacancy creation, worker flows and labor market policies. Importantly, we find that under the widely used period-by-period Nash bargaining protocol, the model generates a counterfactual relationship between workers' job separation expectations and wages. Instead, a wage setting process with less frequent wage renegotiations is found to be empirically consistent. Moreover, we show that the presence of biased beliefs can qualitatively alter the equilibrium effects of labor market policies. Lastly, when allowing for biased firms' beliefs, we establish that only the difference between firms' and workers' biases matters for the bargained wage but not the size of biases.
Keywords: E24; J64; D84; 330; subjective expectations; labor markets; search and matching; bargaining; policy